An evaluation of cardiac murmurs in new-born - Pillai, Preethi S.; Narayanan, Neelima; Chacko, Lyla (International Journal of Contemporary Pediatrics, 2017)
Background: Congenital heart disease (CHD) is defined as a structural abnormality of the heart or intrathoracic great vessels that is actually or potentially of functional significance. The aim of the study is to assess the prevalence of congenital heart disease in new-borns with cardiac murmurs and to study the spectrum of cardiac diseases in new-borns with cardiac murmur. Methods: All the new-borns with cardiac murmurs were evaluated with ECG, Chest X ray and ECHO. They were classified into normal, mild, moderate and severe heart disease. Results: Of the 3375 babies analysed, 80 babies had murmur. ECHO could not be done in 8 babies. Of the 72 babies, 75% of new-borns with murmur had cardiac disease. The prevalence of cardiac disease in this population is 16 per 1000 new-borns. The prevalence of cardiac disease in new-borns with murmur is 750 in 1000 new-borns .94.5% had acyanotic heart disease and 5.5% had cyanotic heart disease. VSD was the most common lesion. 13.9% had severe heart disease, 20.8% had moderate heart disease and 40.3% had mild cardiac disease. There was good correlation between the degree of murmur and the severity of the cardiac disease. Chest X ray contributed only 12.5% to diagnosis of cardiac disease and ECG contributed only 5.3% to the diagnosis. If both ECG and Chest X ray were abnormal,there was 100% association with significant cardiac disease. No correlation was found between gestational age and birth weight and severity of heart Disease. Conclusions: Present study has proved that any murmur in newborn requires evaluation with ECHO as 75% of new-borns with audible murmur had cardiac disease of which 34.7% was moderate to severe heart disease. Abnormal ECG and Chest X ray was 100% associated with severe heart disease.